Analisis Pengaruh Kebijakan Bank, Kemudahan Akses, dan Efektivitas Iklan terhadap Minat Masyarakat Menggunakan Layanan Perbankan Syariah di Kota Medan - Rezky Zazilah Harahap; Nurul Aulia Harahap; Dewi Tamora Siregar (Indo Publishing, 2026)
This study aims to analyze the influence of bank policies, ease of access, and advertising effectiveness on the interest of the people of Medan City in using Islamic banking services. The theoretical framework used is the Theory of Planned Behavior (TPB), with three independent variables: Islamic bank policy, ease of access, and advertising effectiveness, and usage interest as the dependent variable. The research employs a quantitative approach with a survey method involving 30 Muslim respondents in Medan City selected through purposive and accidental sampling techniques. Data were analyzed using multiple linear regression. The results indicate that all three variables have a positive and significant influence on public interest, both partially and simultaneously. Islamic bank policy is the dominant factor, followed by advertising effectiveness and ease of access. The research model explains 97.8% of the variation in interest with an R² value of 0.978. The implications of this study emphasize the importance of strengthening sharia policies, optimizing physical and digital access, and developing educational and sharia-compliant marketing communication strategies to enhance public interest in Islamic banking.